Capturing lessons for sustainable tourism planning and research: evidence and a call for a context-based management theory - Rubiños Vieira, Cathy Alida (2022)
Although Sustainable Tourism (ST) represents a positive approach for community development, its implementation is challenging. Institutional strategies may work well in one location but not in another, making it necessary to develop context-based ST management theory to provide some guidance for tourism development. Such theory can only be built with the accumulation of knowledge from cases where a combination of institutional arrangements and context-specific characteristics showed to be - or not – sustainable. We show, however, how ST research is fragmented, challenging the comparison of results. We adapt and propose The Coupled Infrastructure System Framework (CISF) as a tool for tourism research to integrate efforts. With its guidance, we perform a qualitative meta-analysis. Ninety case studies were systematically coded and analyzed to identify linkages between context characteristics, institutions, and outcomes. We found studies to have mostly positive (N=14), mostly negative (N=7), or mixed (N=69) ST outcomes. Our analysis suggests that five contextual characteristics are overall linked to negative outcomes: high tourists' affluence, preexisting asymmetries in the community, short and long (as opposed to medium) development stages, high seasonality, and foreign influence. We studied how developers avoid unsustainable outcomes with different institutional strategies in exceptional cases. We also found that when categorized by the degree of community involvement in tourism development, cases with the highest rates of positive social and environmental outcomes were those with the highest involvement level: communities are tourism developers. However, higher rates were found for positive economic outcomes when communities participated in the decision-making process but did not act as managers. This study contains theoretical contributions in identifying knowledge gaps, illustrating the adaptation of the CISF to ST research, and identifying thematic categories as possible causality of ST outcomes. Moreover, generated knowledge can assist tourism developers in the challenge of managing tourism sustainably.